2009
DOI: 10.1212/01.wnl.0000336370.51010.a1
|View full text |Cite
|
Sign up to set email alerts
|

Practice Parameter: Evaluation of distal symmetric polyneuropathy: Role of laboratory and genetic testing (an evidence-based review)

Abstract: Background: Distal symmetric polyneuropathy (DSP) is the most common variety of neuropathy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

3
190
0
11

Year Published

2012
2012
2016
2016

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 222 publications
(204 citation statements)
references
References 40 publications
3
190
0
11
Order By: Relevance
“…The American Academy of Neurology (AAN) recently published guidelines for the laboratory evaluation of DSP. 3 Based on a systematic review of the literature, the AAN concluded that the tests providing the highest yield are fasting blood glucose levels, serum B12, associated metabolites (methylmalonic acid and homocysteine), and serum protein electrophoresis. For those with a sensory predominant neuropathy, a glucose tolerance test could be considered.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The American Academy of Neurology (AAN) recently published guidelines for the laboratory evaluation of DSP. 3 Based on a systematic review of the literature, the AAN concluded that the tests providing the highest yield are fasting blood glucose levels, serum B12, associated metabolites (methylmalonic acid and homocysteine), and serum protein electrophoresis. For those with a sensory predominant neuropathy, a glucose tolerance test could be considered.…”
mentioning
confidence: 99%
“…5 Despite the recent AAN recommendations and the publication of several clinical approaches to the evaluation of neuropathy, clinicians continue to order a wide variety of laboratory tests. [3][4][5][6][7] In this study, we evaluated the frequency of abnormal thyroid or rheumatologic results in the setting of a diagnosis of peripheral neuropathy. When the tests were abnormal, we assessed the frequency that the test changed the suspected etiology or management.…”
mentioning
confidence: 99%
“…By comparison, non-neurologists had much lower utilization of MRIs and electrodiagnostic tests, but also had lower utilization of AAN-recommended laboratory tests for neuropathy, 12 and SPEP have been shown to have a substantial yield in neuropathy presentations and abnormal results influence further relevant management including specific treatments. 8,11,12 This result highlights the fact that more testing does not equate with overutilization. Furthermore, the low utilization of AANrecommended tests by all provider types emphasizes the opportunity we have to improve the care of many patients with neuropathy.…”
Section: Test Utilizationmentioning
confidence: 87%
“…While peripheral neuropathy comprises many different subtypes that may affect what constitutes appropriate testing, the vast majority of patients have a distal symmetric polyneuropathy. 8 Recently, the AAN published a systematic review of diagnostic testing in distal symmetric polyneuropathy, and found evidence to support routine testing with serum protein electrophoresis (SPEP), B 12 , fasting glucose test, and glucose tolerance test (GTT). 8 However, the strength of the evidence is modest (Class C), and the review does not address other commonly ordered tests for this condition, including MRIs of the neuroaxis and electrodiagnostic tests.…”
mentioning
confidence: 99%
See 1 more Smart Citation